Assessment of the Effectiveness of Transcranial Magnetic Stimulation in Subjective Tinnitus - Aydın, Mesut; Erkan, Mustafa; Gündoğdu, Ramazan; Vural, Alperen; Kökoğlu, Kerem; Şahin, Mehmet İlhan (International Archives of Otorhinolaryngology, 2020)
Introduction Increases in spontaneous activity in the neurons of the auditory cortex are presumed as the pathophysiology of tinnitus.Objective To investigate the effectiveness of transcranial magnetic stimulation (TMS) in the treatment of tinnitus.Methods A total of 62 patients between the ages of 22 and 74 with chronic subjective tinnitus were enrolled in the study. The inclusion criteria were normal findings on an otolaryngologic examination and normal ranges of complete blood count, routine biochemical parameter levels, thyroid function, air-bone gap on pure-tone audiometry, and middle-ear pressure and stapedial reflex on tympanometry. The patients were randomized into 2 groups: 40 patients were placed in the treatment for TMS (tTMS) group, and the rest (22 patients) were placed in the sham TMS group. The frequency and severity of the tinnitus, as well as the tinnitus handicap inventory (THI) score of each patient were measured before and one month after the treatment, and the values were statistically evaluated.Results We observed a statistically significant improvement in the tTMS group (p < 0.05 and p < 0.05 respectively) regarding the THI and tinnitus severity scores. The sham TMS group showed no significant improvement in terms of the THI (p > 0.05). However, the tinnitus severity showed a significant increase in this group (p < 0.05). The comparison of differences in the changes in the THI and the tinnitus severity scores showed a significant statistical improvement in the tTMS group compared with the sham TMS group (p < 0.05 and p < 0.05 respectively).Conclusion Transcranial magnetic stimulation was found to be effective in the treatment of tinnitus, and may be adopted as a treatment for tinnitus after further comprehensive studies.
Keywords: sham group; tinnitus; tinnitus handicap inventory